Living in a hamster wheel: Identity construction through hopes and terrors in Bong Joon-Ho’s 'Parasite' (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Bong Joon-Ho’s Parasite (2019) has successfully depicted universal issues regarding class identity and social mobility. It tells us a story about a lower-class family, the Kims who aspired and struggled in their journey of climbing the social ladder. This research aims to explore the process of identity construction of the Kims. Close textual analysis is employed as a tool for investigation and Althusser’s ideological interpellation is used to explain the process. The research also focuses on the socio-cultural factors that influence the Kims’ social mobility which contribute to the permanence of their class identity. The findings found out that many symbolic markers such as differences in property, neighborhood, education, diet and behavior distinguish the lower- and upper-class families. Thus, interpellation occurs when the family is lured into believing the ‘American dream’: by working hard enough and taking more risks, it is possible to climb up the social hierarchy. It constructs their identity as a lower-class with aspirations to move upward. This study also concludes that the persistence of social immobility is highly influenced by the level of education, perceptual discrimination, the impossibility of cross-class marriage and the economic inequality. Therefore, it proves that class identity can be unfavorable inheritance.